THE POLITICAL ROLE OF THE UNITED STATES IN THE DEFAULT OF ARGENTINA - Miranda, Roberto (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
In December of 2001, due to the financial crisis, Argentina had to suspend external payments. The country started a frantic process of abandonment of default thereafter. Research about the causes, processes, and mechanisms of the crisis has been focused on economic issues. The present work instead considers international politics. The aim of the paper is to analyze the role of the United Sates in the restructuring of Argentina’s debt. We consider the reasons, conditions, and actions developed by the hegemonic power in the relationship between Argentina and its creditors. We specially emphasize the political role played by the US government, a position that the US administration had no intention to assume neither before the debacle nor after the crisis started. We conclude that, despite the fact that Argentina has overcome the most difficult part of its default, the episode made evident, once more, the strong Argentine dependence towards the United States.